THE CONTROVERSY OF "TECHNOCRACY" AND "HUMANISTIC COMMUNITARIANISM" AS WORLDVIEW PRINCIPLES - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article considers the contradictions of technological determinism and technocratic thinking principles, is debated problem of correlation between the real and the virtual, artificial and alive on the basis of the works of Erich Fromm, St. Lem and D. Bell. It is shown that the integrity of the person theoretically is held on the basis of the humanistic communitarian’s principle.